2005
DOI: 10.1021/jm049133b
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Screening for β-Secretase (BACE1) Inhibitors Reveals the Importance of Protonation States at Asp32 and Asp228

Abstract: A comparative virtual screen for beta-secretase (BACE1) inhibitors using different docking methods (FlexX and FlexX-Pharm), scoring functions (Dock, Gold, Chem, PMF, FlexX), protonation states (default and calculated), and protein conformations (apo and ligand bound) has been performed. Apo and ligand bound conformations of BACE1 were both found to be suitable for virtual screening. Assigning calculated protonation states to catalytic Asp32 and Asp228 residues resulted in significant improvement of enrichment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
104
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(112 citation statements)
references
References 32 publications
6
104
2
Order By: Relevance
“…The change in pKa values causes protons to be released or consumed upon binding [99][100][101][102][103][104][105]. The changes in pKa values of the ligand and the protein upon complexation are therefore of importance to the affinity of the drug [106] , and pKa calculations of protein and ligand titratable groups should thus be integrated into docking and screening algorithms [107,108].…”
Section: Ph-dependence Of Protein-ligand Bindingmentioning
confidence: 99%
“…The change in pKa values causes protons to be released or consumed upon binding [99][100][101][102][103][104][105]. The changes in pKa values of the ligand and the protein upon complexation are therefore of importance to the affinity of the drug [106] , and pKa calculations of protein and ligand titratable groups should thus be integrated into docking and screening algorithms [107,108].…”
Section: Ph-dependence Of Protein-ligand Bindingmentioning
confidence: 99%
“…This approach constrains the QM/MM calculations to be consistent with the Xray diffraction data. We have chosen the 1FKN structure as the basis for our calculations because it is a relatively high-resolution crystal structure and has been studied very extensively in previous theoretical investigations [19][20][21] . Under the constraint of the X-ray diffraction data, we will construct a set of all-atom models containing the coordinates for hydrogen atoms in the 8 protonation states defined in Figure 3, and use an accurate energy function to identify the most probable one.…”
Section: Introductionmentioning
confidence: 99%
“…Polgár and Keserü also demonstrated that the choice of protonation state, both for the enzyme [Polgár and Keserü , 2005] and for the ligand [Polgár et al, 2007], can have a significant effect on the retrieval of actives in a virtual screen. In the 2005 study, they employed an apo (PDB entry 1SGZ) and the OM99-2 liganded crystal structure with two docking methods (FlexX and FlexX-Pharm) and five scoring functions (Dock, GOLD, Chem, PMF, and FlexX).…”
Section: Protonation Statementioning
confidence: 98%
“…In addition, Polgár and Keserü [2005] have computed the pKa values for all titratable residues in BACE-1 using ZAP. They suggest that at low pH, the diprotonated form (e.g., configurations F, G, or H in Fig.…”
Section: Protonation Statementioning
confidence: 99%